Prolonged survival of transplanted stem cells after ischaemic injury via the slow release of pro-survival peptides from a collagen matrix. (February 2018) - Lee, Andrew; Inayathullah, Mohammed; Lijkwan, Maarten; Zhao, Xin; Sun, Wenchao; Park, Sujin; Hong, Wan; Parekh, Mansi; Malkovskiy, Andrey; Lau, Edward; Qin, Xulei; Pothineni, Venkata; et al.
Abstract Stem-cell-based therapies hold considerable promise for regenerative medicine. However, acute donor-cell death within several weeks after cell delivery remains a critical hurdle for clinical translation. Co-transplantation of stem cells with pro-survival factors can improve cell engraftment, but this strategy has been hampered by the typically short half-lives of the factors and by the use of Matrigel and other scaffolds that are not chemically defined. Here, we report a collagen–dendrimer biomaterial crosslinked with pro-survival peptide analogues that adheres to the extracellular matrix and slowly releases the peptides, significantly prolonging stem cell survival in mouse models of ischaemic injury. The biomaterial can serve as a generic delivery system to improve functional outcomes in cell-replacement therapy. The slow release of pro-survival peptide analogues crosslinked to an injectable collagen–dendrimer biomaterial significantly prolongs the engraftment and survival of transplanted stem cells in mouse models of ischaemic injury.